Etika Guru Terhadap Penggunaan AI dalam Pembelajan PAI di Raudhatul Athfal - Meleza Andora; Salwa Aurumia Firanti; Saipul Annur; Afriantoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teachers’ ethics in the use of Artificial Intelligence (AI) in Islamic Religious Education (IRE) instruction at Raudhatul Athfal Gummi. The study employs a qualitative, descriptive approach, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The research subjects include IRE teachers and the school principal, who were selected through purposive sampling. The results indicate that AI is utilized as a learning support tool, particularly in developing instructional materials, creating interactive media, and enhancing student engagement. However, the use of AI is not without ethical challenges, such as the potential for technological dependency and a reduction in humanistic interaction. Therefore, teachers serve as ethical gatekeepers tasked with filtering content, aligning materials with Islamic values, and maintaining a balance between technology and direct interaction. From the perspective of maqasid al-shari‘ah, the use of AI reflects the principle of public interest through the protection of religion, reason, and future generations. This study emphasizes that the integration of AI into Islamic Education must be under the ethical control of teachers to ensure it continues to support the development of students’ character and spiritual values.